The Cultural Identity of Nusantara in a Movie Entitled Sang Pencerah by Hanung Bramantyo - Puspitasari, Dyah Gayatri; Sabana, Setiawan; Ahmad, Hafiz Aziz (Harmonia: Journal of Arts Research and Education, 2016)
Nowadays, during this intercultural era and global challenge, film can be interpreted as a practical strategy to develop meaning and Indonesian cultural identity. Through many singers of audiovisual creation, film has not only served as entertainment, but can also act as an instrument to reflect local values and traditional perspective through the storytelling that has been presented by film director. This role is a significant point to develop local insight and cultural value as the identity of Indonesian film. Although, at some point, this strategy still becomes a problem in Indonesian film fields. Sang Pencerah film that was directed by Hanung Bramantyo is one of Indonesian films that attempted to deliver local identity in its storytelling. This research is an endeavour to identify Indonesian cultural identity that has been represented through Sang Pencerah film. By applying cultural studies and interdisciplinary as their methods, the researchers acquired some interesting findings. Firstly, aesthetic and thematic elements in the film narrative had a significant relation to traditional and cultural values of Javanese society. Secondly, the meaning of cultural identity also had a linear proportion to spiritual values in life, such as determination, peacefulness, gloriness, tolerance, as well as social understanding. Therefore, it can be concluded that the Sang Pencerah film is a manifestation of Hanung Bramantyo regarding to the meaning of Indonesian culture that is based on Javanese society’s local wisdom.How to Cite: Puspitasari, D. G., Sabana, S., Ahmad, H. A. (2016). The Cultural Identity of Nusantara in a Movie Entitled Sang Pencerah by Hanung Bramantyo. Harmonia: Journal of Arts Research And Education, 16(1), 57-65. doi:http://dx.doi.org/10.15294/harmonia.v16i1.6768